Modelling profit-loss-sharing contracts in investment financing - Abdul Jalil, Mohd Aisha Nuddin (2018)
Excessive debt poses many serious problems to individuals, firms and countries. We have seen many world economic crises, many of which are the results of debt. Countries which have high amount of sovereign debt are in danger of being declared bankrupt nations. These countries have to borrow more to cover their present debts. Islam as a way of life prescribes a solution to this problem by advocating equity based financing. Islam does not ban debt but the religion offers another alternative to debt financing that is the equity based financing. Instruments of Islamic commercial financing are based on two principles which are: the profit-loss-sharing (PLS) principle which is equity based financing and the mark-up principle (use of debt like instruments). Unfortunately, in today’s practice, there is an imbalance between profit-loss-sharing modes of financing and mark-up based financing. Mark-up based financing dominates the Islamic financial markets while equity based financing is almost negligible. Analysis of these two modes of financing is needed in understanding and hopefully correcting the situation. This study analyses four main issues related to profitloss- sharing (PLS) and non-PLS modes of financing. The first is related to the optimality in the usage of PLS compared to non-PLS. PLS is said to be less desirable by banks due to moral hazard issues. Using two periods of simple debt-plus-equity financing model with probability of defaulting in both periods, the necessary and sufficient conditions for the optimality of PLS (Mudharabah and Musyarakah) and non-PLS contracts (Murabahah) are constructed and analysed. The result shows that without collateral, PLS contract satisfy all the incentive compatibility and limited liability conditions. The moral hazard risk faced by the bank in maximizing the bank profit for PLS contract is also not much different from the non-PLS contracts. Thus, PLS contract is the optimal contract for banks with respect to any level of moral hazard of the contract environment. This result contradicts the result obtained by Aggarwal and Yousef (2000) in which the authors found that the mark-up based financing is optimal in high moral hazard environment even if it is not secured by collateral. The second issue discussed in this study relates to the effect of collateral and monitoring on the PLS and non-PLS contracts. In addition, the effect of collateral on the entrepreneur, the bank and also the society are investigated. It is found that collateral aids in making the non-PLS contract as the optimal contract for the banks but not for the entrepreneur. It is also found that the Pareto optimal contract which benefits both the bank and entrepreneur is the PLS contract without collateral in which the monitoring cost should be borne by the business cash flow. The third issue relates to the measurement of moral hazard in PLS and non- PLS contracts. A new moral hazard index based on the entrepreneur’s utility function is designed which quantifies the moral hazard faced by a bank in a given set of loan contract. This index is capable of complementing the current techniques in estimating the credit risk of a one-period loan contract. Using the threshold of the index together with the firm gearing ratio, this study also shows that the PLS contract aids in reducing the financial risk of firms. A systematic method is needed in measuring and understanding the progress in the development of Islamic financial instruments. The fourth issue discussed relates to this purpose, it addresses the issue of the competitiveness of Islamic financial instruments relative to the conventional instruments in a country. The widely employed descriptive Constant Market Share (CMS) analysis tools normally used in analysing competitiveness of exports of a country with respect to other countries in a region or the world are based on general mathematical identities. As the identities are originated from the product rule for the differentiation of product of two functions and relate to changes in shares of entities out of the total share in discrete case, thus it can be explored to be used for other fields other than the change in exports. This study demonstrated how the analysis can be used in analysing the competitiveness of different modes of investment instruments in a country. In this study the Constant Market Share (CMS) tool is described within a new geometric setting. This new approach allows researchers to overcome the traditional unsolvable index number inconsistency problem. Subsequently, CMS competitiveness index constructed from the geometric framework is able to measure the competitive performance of PLS instruments. The solution proposed using the traditional CMS tool is easy to be understood and interpreted while it illustrates changing patterns of PLS competitiveness aggregated across countries or regions.